The administration of hCG or GnRH induce the formation of accessory corpora lutea - Fernández, J. (2017)
The aim of this study was to evaluate the effect of the administration of hCG or GnRH at day 4 post fixed-time artificial insemination (FTAI) on the formation of accessory corpora lutea (acc-CL) and the concentration of serum progesterone (P4) in sheep. Multiparous adult Merino ewes (n=36) were treated for estrus synchronization using two intramuscular (i.m.) injections of prostaglandins (PG, 125 μg Cloprostenol, Cyclase®, Syntex, Argentine) with an interval of 14 days. At 53-56 h after the second PG application, FTAI was performed vaginally with a dose of 100 million spermatozoa of fresh semen.